To regulate or not to regulate South African podcasts? A qualitative study on cultural expression - Theledi, Kamogelo Tinyiko (University of the Witwatersrand, Johannesburg, 2024)
This research is a qualitative study that explores the grey area of podcast regulation in South Africa. Furthermore, this study assesses the role played by platform and government policies in the cultural expression of South African podcasts. The study undertakes the constructivism worldview as it looks at the podcast phenomenon through the lens of three podcasts. This research employs a qualitative multi-case study approach, and interviews are conducted with following case studies to achieve its objectives; Volume Africa, King David Studio and Nkululeko n Cultr podcasts. The aim of this research is to traverse to what extent has the influence of the non- regulation of South African podcasts had on cultural expression as well as to assess the role that government as well as platform policies play in the cultural expression of these podcasts. In the past 10 years podcasting has expanded rapidly as a popular cultural phenomenon, in particular, South African podcasts have allowed for the documenting and dissecting of cultural and societal issues (Mkhabela 2021). African podcasters use a variety of techniques and formats to showcase their shows ranging from diverse heritage, language, culture, and style. This study finds that the regulation of podcasts has become a mammoth task for South African broadcasting regulatory bodies. The study has also found that regulatory frameworks like those found in the Film and Publications Amendment Act of 2019 have become more reactive than proactive when regulating podcasts. Even though podcasts do not fall into the traditional broadcasting parameters, they still face some restrictions and regulations enforced by audiences, advertisers, and social media platforms.
A research report Submitted in fulfillment of the requirements for a Master of Arts, In the Faculty of Humanities , School of Arts, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; South African podcasts; cultural expression; SDG-4: Quality education